2021
DOI: 10.1002/cjoc.202100386
|View full text |Cite
|
Sign up to set email alerts
|

Maleimide Chemistry: Enabling the Precision Polymer Synthesis

Abstract: Herein is presented a compilation of the main characteristics of maleimide chemistry in developing the precisely controlled polymers, including the design of sequence‐controlled polymers, topological polymers, and polymeric single‐chain nanoparticles. The synthetic methods, relied on the versatilities of the maleimide moieties as a latent monomer which leads to an efficient alternative in various innovative applications, especially in self‐healing material, self‐reporting materials for real‐time monitoring, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, homopolymerisation must be carefully considered, particularly for the SUMI of maleimide derivatives. 41,42 Furthermore, slow indene addition can be an issue when using indene for SUMI, especially at lower stoichiometries. 40 Thus, we acknowledge that some impurities and side-reactions could lead to difficulties in isolating a perfectly discrete product.…”
Section: Resultsmentioning
confidence: 99%
“…However, homopolymerisation must be carefully considered, particularly for the SUMI of maleimide derivatives. 41,42 Furthermore, slow indene addition can be an issue when using indene for SUMI, especially at lower stoichiometries. 40 Thus, we acknowledge that some impurities and side-reactions could lead to difficulties in isolating a perfectly discrete product.…”
Section: Resultsmentioning
confidence: 99%
“…N-phenylmaleimides substituted by the N atom present various reactivity and photochemical properties that depend on the substituent group and the torsion angle between imide and benzene rings. These molecules have been used as a copolymer, providing greater structural rigidity, increase in dielectric properties and thermal stability compared to the unreacted polymer (Mejia et al, 2021;Shi et al, 2020). The importance of these molecules is due to the potential reactivity of the double bonds that act as dienophiles, promoting Diels-Alder reactions for the formation of new organic molecules (Galkin et al, 2022;Bastin et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Reversible‐deactivation radical polymerization (RDRP) [ 4‐6 ] is a powerful method for precise synthesis of polymers. [ 7‐9 ] In recent years, as enlightened by the importance of MWDs, considerable efforts have been made to regulate MWDs via RDRP (Figure 1a). [ 2 ] For example, the Fors group has carried out systematic studies to tailor the shapes of MWDs, [ 10‐11 ] and revealed their striking impacts on properties.…”
Section: Background and Originality Contentmentioning
confidence: 99%